AB0800 Changes of body composition in myositis patients are associated with disease duration, inflammatory status, skeletal muscle involvement and physical activity. (12th June 2018) - Oreska, S.; Spiritovic, M.; Cesak, P.; Marecek, O.; Storkanova, H.; Smucrova, H.; Hermankova, B.; Kubinova, K.; Klein, M.; Vernerova, L.; Ruzikova, O.; Becvar, R.; et al.
Abstract : Background: Idiopathic inflammatory myopathies (IIM) are characterised by inflammation and atrophy of skeletal muscles, pulmonary and articular involvement, which limit the mobility/self-sufficiency of patients, and can have a negative impact on body composition. Objectives: To assess body composition and physical activity of IIM patients and healthy controls (HC). Methods: 54 patients with IIM (45 females/9 males; mean age 57.7; disease duration 5.8 years; polymyositis (PM, 22)/dermatomyositis (DM, 25)/necrotizing myopathy (IMNM, 7)) and 54 age-/sex-matched HC (45 females/9 males, mean age 57.7) without rheumatic diseases were included. PM/DM patients fulfilled Bohan/Peter criteria for PM/DM. Anthropometric parameters and body composition were assessed (by densitometry: iDXA Lunar, and by bioelectric impedance: BIA2000-M), and physical activity was evaluated using Human Activity Profile (HAP) questionnaire. Routine biochemistry analysis was performed after 8 hours of fasting. Muscle involvement was evaluated by manual muscle test (MMT-8) and functional index 2 (FI2). Data are presented as mean ±SD. Results: Compared to HC, patients with IIM had a trend towards significantly increased body fat% as assessed by iDXA (BF%: 39.9±7.1 vs. 42.4%±7.1%, p=0.077), but significantly decreased lean body mass as assessed both by iDXA (LBM: 45.6±8.1 vs. 40.6±7.2 kg, p=0.001) and BIA (LBM: 52.6±8.8 vs. 48.7±9.0 kg, p=0.023), and increased extracellular mass/body cell mass (ECM/BCM) ratio (1.06±0.15 vs. 1.44±0.42, p<0.0001), which reflects worse muscle predispositions for physical exercise, aerobic fitness/performance, and also deteriorating nutritional status. Compared to HC, IIM patients had significantly lower bone mineral density (BMD: 1.2±0.1 vs. 1.1±0.1 g/cm 2, p<0.001). Disease duration negatively correlated with BMD (r=−0.392, p=0.004) and LBM-BIA (r=−0.272, p=0.047). CRP was positively associated with BF% assessed both by DEXA (r=0.276, p=0.035) and BIA (r=0.306, p=0.025). Higher BF%>DEXA was associated with worse physical endurance (FI2: r=−0.311, p=0.026) and worse ability to perform physical activity (HAP: r=−0.292, p=0.032). MMT-8 score negatively correlated with ECM/BCM ratio (r=−0.385, p=0.006). Conclusions: Compared to healthy age-/sex-matched individuals we found significant negative changes in body composition of our IIM patients, which are associated with their disease duration, inflammatory status, skeletal muscle involvement, and physical activity, and could reflect their impaired nutritional status and predispositions for physical exercise, aerobic fitness and performance. Acknowledgements: Supported by AZV-16–33574A and SVV-260373. Disclosure of Interest: None declared